Immunological balance between Treg and Th17 lymphocytes as a key element of type 1 diabetes progression in children - Starosz, Aleksandra; Jamiołkowska-Sztabkowska, Milena; Głowińska-Olszewska, Barbara; Moniuszko, Marcin; Bossowski, Artur; Grubczak, Kamil (Frontiers in Immunology, 2022)
Type 1 diabetes (T1D) is an autoimmune destruction of the beta cells of pancreatic islets. Due to complexity of that disease, the mechanisms leading to the tolerance breakdown are still not fully understood. Previous hypothesis of imbalance in the Th1 and Th2 cells as the main contributing factor has been recently changed towards role of other lymphocytes – regulatory (Treg) and IL-17A-producing (Th17). Our study aims to assess changes within Treg and Th17 cells in newly diagnosed T1D pediatric patients and their association with the disease remission. Flow cytometry implementation allowed for Treg and Th17 analysis in studied groups and further combination with clinical and laboratory data. In addition, expression of diabetes-related genes was tested and evaluated in context of their association with studied lymphocytes. Initial results revealed that Treg and Th17 are significantly higher in T1D than healthy controls. Patients with lower HbA1c and daily insulin requirement demonstrated higher levels Tregs. Similar tendency for insulin intake was also observed in reference to Th17 cells, together with high levels of these cells in patients demonstrating higher values for c-peptide after 2 years. In low-level Treg patients, that subset correlate with the c-peptide in the admission stage. In addition, higher levels of IL-10 were associated with its correlation with HbA1c and insulin dosage. In context of genes expression, strong associations were demonstrated in T1D subjects inter alia between RRAD and Th17 or Treg cells. Cumulatively, our data indicate possible novel role of Treg and Th17 in mechanism of type 1 diabetes. Moreover, potential prognostic value of these populations has been shown in reference to diabetes remission.